1987
DOI: 10.1080/00223980.1987.9712660
|View full text |Cite
|
Sign up to set email alerts
|

Depression During and Following Pregnancy: Quality of Family Relationships

Abstract: Fifty-four primiparous women were administered the Zung Self-rating Depression Scale and the Objective Social Perception Inventory during the last trimester of pregnancy. Four to 8 weeks postpartum, they again responded to the SRDS. A poor relationship with the husband, as rated during pregnancy, was significantly associated with depression during pregnancy and was also predictive of depression after childbirth. No parallel association between relationship with the mother and depression pre- or postpartum was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…This decision was based on the fact that all the risk factors included in the definition were shown to be strongly interrelated in this same sample, and purely separate groups would have been very small (Pajulo, Savonlahti, Sourander, Helenius, & Piha, 2001b, 2001c. The coexistance of these risk factors has also been described also in previous studies (Burns, Melamed, Burns, Chasnoff, & Hatcher, 1985;Dimitrovsky, Perez-Hirshberg, & Itskovitz, 1987). Although the authors' original interest specifically concerned substance-dependent mothers, the findings made it more relevant to widen the definition of risk group in this sample.…”
Section: Limitationsmentioning
confidence: 58%
“…This decision was based on the fact that all the risk factors included in the definition were shown to be strongly interrelated in this same sample, and purely separate groups would have been very small (Pajulo, Savonlahti, Sourander, Helenius, & Piha, 2001b, 2001c. The coexistance of these risk factors has also been described also in previous studies (Burns, Melamed, Burns, Chasnoff, & Hatcher, 1985;Dimitrovsky, Perez-Hirshberg, & Itskovitz, 1987). Although the authors' original interest specifically concerned substance-dependent mothers, the findings made it more relevant to widen the definition of risk group in this sample.…”
Section: Limitationsmentioning
confidence: 58%
“…The incidence rate found in the present study is also comparable to results of studies in which other self-report scales were used to estimate the incidence of postpartum depression. Such fiidings include studies using the Zung Depression Scale [Dimitrovsky et al (1987) (31,4%, N = 54) and Hayworth et al (1980) (22%, N = 127), as well as the R a s h Three-Area Depression Scale (Paykel et al, 1980) (20%, N = 120)l.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Zung SelfRating Depression Scale (Zung, 1965) incidence rates of 31,4% (Dimitrovsky, Perez-Hirshberg & Itskowitz, 1987) and 22% (Hayworth, Little, Carter, Raptopoulos, Priest & Sander, 1980) were found. Paykel, Emms, Fletcher and Rassaby (1980) employed the R a s h Three-Area Depression Scale ( R a s h , Shulterbrandt, Reatig & McKeon, 1970) and found that 20% of their subjects were depressed.…”
mentioning
confidence: 99%
“…Emotional detachment and deficits in interpersonal relationships are common in women suffering from depression (Dimitrovsky et al, 1996;Kitamura et al, 1996). Thus, researchers have posited that lower maternal attachment represents an additional form of emotional detachment (Condon & Corkindale, 1997).…”
Section: Introductionmentioning
confidence: 99%